Baciyan-ı Rum ve Anadolu Tasavvufundaki Yeri - Çubukçu, Hatice (FSM Vakıf Üniversitesi, 2015)
Bâciyân-ı Rûm XIII. yüzyıl Anadolu’sunda göçmen Türkmen hanımların oluşturduğu bir gruptur. Bu isimle ilk olarak onlardan bahseden XV.yüzyıl Osmanlı tarihçisi Âşıkpaşazâde’dir. Ne var ki, diğer tarihî kaynaklarda doğrudan böyle bir teşkilattan sözedilmediği için Bâciyân-ı Rûm’un mahiyeti tam olarak aydınlatılamamıştır. Mevcut bilgilerden yola çıkarak; Bâciyân-ı Rûm’un, Hacı Bektâş-ı Velî’nin manevî desteğiyle sufi Türkmen hanımlarca kurulmuş, halka hizmeti esas almış bir teşkilat olduğunu söyleyebiliriz. Dolayısıyla bu sufi Türkmen hanımların Anadolu’nun İslâmlaşmasında ve Türkleşmesinde önemli katkıları olmuştur.

Bâciyân-ı Rûm is an 13th century Anatolian mystic group made up of Turkoman immigrating women. Aşık Pahsa Zade is the first Otoman historian to mention this group with this name. However, the true nature of this organization ‘Bâciyân-ı Rûm’ has yet to be well understood, for other histroical sources do not directly mention such a mystic organization. Based on the present knowledge in hand, it can be sateted that the organization ‘Bâciyân-ı Rûm’ was established by suphist Turkoman women with the sipritual support of Hacı Bektaş Veli for the purpose of public service. It can, therefore, be said that these Turkoman female suphists helped, to a large extent, Anatolia to embrace become Muslims.
Bacıyan-ı Rum and Her Place in the Anatolian Sufism
Keywords: Fütüvvet; Zaviye; Keramet; Derviş; İsar; Futuvva; lodge; Karamah; Darwish; Altruism